Diabetes Mellitus: a risk factor for drug toxicity - Martins, Anna Luiza Chimirri de Limas (2019)
Objective: To assess the effect of the antibiotic Gentamicin in an experimental model in the presence of Diabetes Mellitus through renal function and oxidative profile. Method: Adult male Wistar rats were distributed into groups: Citrate; Gentamicin (Genta), (intraperitoneal, i.p. gentamicin, 100 mg/kg of body weight, once a day,5 days); DM (60 mg/kg of STZ (Streptozotocin), single dose, intravenously, i.v., diluted in citrate buffer); and DM+Genta. Physiological parameters, renal function (creatinine clearance), oxidative damage (peroxides and thiobarbituric acid reactive substances – urinary TBARS) and renal hemodynamics were evaluated. Results: The Diabetes Mellitus group presented chronic hyperglycemia associated with loss of body weight, polyphagia, polydipsia and polyuria, in addition to reduced renal function and with an increase in oxidative metabolite excretion. Administration of gentamicin induced a reduction in renal blood flow and increased renal vascular resistance in healthy rats. The association of Diabetes Mellitus with gentamicin resulted in an additional reduction in renal function and elevation of oxidative metabolites, with increased renal vascular resistance. Conclusion: The existence of Diabetes Mellitus resulted in an elevation of gentamicin nephrotoxicity, thus confirming the risk factor for drug nephrotoxicity.